Implementasi of The Covid-19 Health Protocol at Beauty Salons in Sangir District, Solok Selatan Regency - Friska Adela; Linda Rosalina (Universitas Negeri Padang, 2022)
Compliance with the implementation of health protocols must continue to be improved in order to break the chain of transmission of Covid-19. One of them is a beauty salon in Sangir District, Solok Selatan Regency. Beauty salon is a place of business engaged in the field of beauty related to care such as hair, face, and body care without any surgery. This study aims to: a) find out the personal hygiene of employees at beauty salons in sangir sub-district of Solok Selatan regency, b) know the sanitation of beauty salons in beauty salons in sangir sub-district of Solok Selatan regency and c) know the implementation of covid-19 health protocols in beauty salons in sangir district of Solok Selatan regency. This type of research is quantitative descriptive research. The population in this study were leaders, employees, and visitors to beauty salons located in sangir sub-district, Solok regency with a total sample of 49 people. The type of data in this study is primary data with data collection techniques using observations, interviews, and questionnaires. The data analysis technique uses a percentage formula and then the calculation of the respondent's achievement rate (TCR) is carried out. Based on the results of the study, personal hygiene of employees at beauty salons in sangir district, Solok Selatan regency, was considered very good with a percentage value of tcr of 93.51%, sanitation at beauty salons in sangir district, Solok Selatan regency was considered good with a percentage value of tcr of 84.69% and the implementation of covid-19 health protocols in beauty salons in sangir district, Solok Selatan regency was considered moderate with a percentage value of tcr of 77.11%. It can be concluded that the implementation of the covid-19 health protocol is not carried out properly, therefore it is recommended for beauty salons to comply with and implement the covid-19 health protocol rules so that the transmission of the covid-19 virus can be prevented